MEKANISME RESISTENSI TERHADAP ANTI MIKROBA - Dona Liazarti (LPPM Universitas Abdurrab, 2022)
ABSTRACT Resistance to antimicrobials is the resistance of microorganisms to antimicrobials that were previously effective against infections caused by these microorganisms. Bacterial resistance to antimicrobials can occur with any drug and is a major problem in the treatment of infections in hospitals and in the community. Infections caused by resistant microorganisms often fail standard treatments, resulting in prolonged treatment period, being more expensive, and even causing death. The mechanisms of bacterial resistance to antimicrobials vary and continue to develop, including antimicrobial inactivation, inhibition of entry of antimicrobials to the target site, changes in target molecules where antimicrobials bind, increased production of target molecules and changes in enzymes that activate antimicrobials. Genetic resistance can be intrinsic or acquired. Acquired resistance mechanisms occur through gene mutations then passed down vertically or through horizontal gene transfer. Mutations can occur spontaneously or adaptively, due to substances present in the environment (mutagens) such as chemicals, radiation and ultraviolet light. The main mechanism for the spread of antimicrobial resistance is by horizontal gene transfer. Genetic material that is transferred in a mobile form is in the form of plasmids, transposons and integrons and can be transferred by various mechanisms including conjugation, transformation and transduction.